House H10 from Marina el-Alamein on the northwest coast of Egypt - Rafał Czerner; Grażyna Bąkowska-Czerner (Polish Archaeology in the Mediterranean, 2020)
House H10 was one of the buildings located in a Hellenistic-Roman city at the Marina el-Alamein site in Egypt, whose relics were the first to be discovered. Successive research, conducted since 1997 along with initial conservation work, has provided a comprehensive overview. The house is one of the largest and most extensive of this site. Its spatial design is a showcase for the technology typical of houses from Marina. The house is embedded in both Greco-Hellenic and Roman traditions. It is an oikos house with a courtyard with two columned porticoes situated symmetrically on either side parallel to the main axis. A third, perpendicular portico, complementing the layout of the incomplete peristyle, is imitated by the architectural decoration of the courtyard elevation, organised by semi-columns. The layout includes two main rooms located opposite each other on two sides of the peristyle. The house was rebuilt several times, which made for a complicated layout. The studies conducted have cast light on domestic religious practice and the distinctive character of the architectural and artistic interior design, including exceptional examples of figural painting. The architecture and décor of the house document the changes occurring at the intersection of Hellenistic and Roman traditions.